2016
DOI: 10.1080/09639284.2016.1218780
|View full text |Cite
|
Sign up to set email alerts
|

Professional competence and continuing professional development in accounting: professional practice vs. non-practice

Abstract: In 2004, the International Federation of Accountants introduced International Education Standard 7 (IES 7), requiring all member professional accounting bodies to adopt mandatory continuing professional development (CPD) schemes. IES 7 places responsibility on individual accounting practitioners to maintain, develop and certify appropriate professional competence. A number of studies have examined practitioner engagement with formal CPD mechanisms and highlighted differing levels of engagement vis-à-vis profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…To theoretically clarify the underlying relationships between the independent and the dependent variables; the current study builds upon the results of previous studies. In this regards, some previous studies (e.g., Halabi & Chowdhury, 2018;Murphy, 2017;Paisey et al, 2007;Paisey & Paisey, 2018;Paisey and Paisey, 2014) indicated that the CPD of accounting, business and financial knowledge have a positive contribution to the quality of the internal audit; likewise, other studies (e.g., Paisey & Paisey, 2018;Tudora, 2013;Mattli & Buthe, 2005;Chersan, 2019;Lee, 1995;Baker, 2005) have indicated that the CPD of the technical competence of the financial auditing has an actual contribution to the quality of the internal audit. Furthermore, a group of studies (Seol et al, 2011;Plant et al, 2019;Kaspina, 2015;Firth et al, 2012;Lenz and Hanh, 2015;Krá l et al, 2017;Siriwardane et al, 2014;Ahmad et al, 2019) showed that the CPD of the professional skills of the internal auditors has a positive contribution to the quality of the internal audit.…”
Section: The Study Modelmentioning
confidence: 90%
“…To theoretically clarify the underlying relationships between the independent and the dependent variables; the current study builds upon the results of previous studies. In this regards, some previous studies (e.g., Halabi & Chowdhury, 2018;Murphy, 2017;Paisey et al, 2007;Paisey & Paisey, 2018;Paisey and Paisey, 2014) indicated that the CPD of accounting, business and financial knowledge have a positive contribution to the quality of the internal audit; likewise, other studies (e.g., Paisey & Paisey, 2018;Tudora, 2013;Mattli & Buthe, 2005;Chersan, 2019;Lee, 1995;Baker, 2005) have indicated that the CPD of the technical competence of the financial auditing has an actual contribution to the quality of the internal audit. Furthermore, a group of studies (Seol et al, 2011;Plant et al, 2019;Kaspina, 2015;Firth et al, 2012;Lenz and Hanh, 2015;Krá l et al, 2017;Siriwardane et al, 2014;Ahmad et al, 2019) showed that the CPD of the professional skills of the internal auditors has a positive contribution to the quality of the internal audit.…”
Section: The Study Modelmentioning
confidence: 90%
“…Martin and Waymire (2017) surveyed accounting students at one public US university to investigate perceptions of the potential earnings, nonmonetary benefits, and financial and job They suggested that, in light of student feedback, the benefits and linkage between academic and practical experiences required more in-depth exploration in the curriculum. Murphy (2017) described the results of interviews with accounting professionals in Ireland regarding the perceptions of work placement and transition back to full-time student and emphasized the need for better management by faculty.…”
Section: Studentsmentioning
confidence: 99%
“…Based on professional skills, accountants can be divided into informed, competent and complete professionals. Investigating practicing and non-practicing Chartered Accountants in Ireland, Murphy (2017) found significant differences in the perception and practice among professionals related to CPD.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%